Comparison of fractionation proteomics for local SWATH library building. Issue 15 (August 2017) - Govaert, Elisabeth; Van Steendam, Katleen; Willems, Sander; Vossaert, Liesbeth; Dhaenens, Maarten; Deforce, Dieter
Abstract : For data‐independent acquisition by means of sequential window acquisition of all theoretical fragment ion spectra (SWATH), a reference library of data‐dependent acquisition (DDA) runs is typically used to correlate the quantitative data from the fragment ion spectra with peptide identifications. The quality and coverage of such a reference library is therefore essential when processing SWATH data. In general, library sizes can be increased by reducing the impact of DDA precursor selection with replicate runs or fractionation. However, these strategies can affect the match between the library and SWATH measurement, and thus larger library sizes do not necessarily correspond to improved SWATH quantification. Here, three fractionation strategies to increase local library size were compared to standard library building using replicate DDA injection: protein SDS‐PAGE fractionation, peptide high‐pH RP‐HPLC fractionation and MS‐acquisition gas phase fractionation. The impact of these libraries on SWATH performance was evaluated in terms of the number of extracted peptides and proteins, the match quality of the peptides and the extraction reproducibility of the transitions. These analyses were conducted using the hydrophilic proteome of differentiating human embryonic stem cells. Our results show that SWATH quantitative results and interpretations are affected by choice of fractionation technique. Data are available via ProteomeXchange with identifier PXD006190.